Irrigation modernization: Chinese style - Report on a field visit to Shijin Irrigation System, Hebei Province [China] - Shah, Tushaar; Mohatadulla, Khalid; Qureshi, Asad Sarwar (International Water Management Institute, 2012)
This Highlight reports on the trip, which included a field visit to newly-modernized Shijin irrigation system in Hebei province. If the Shijin system is any guide, three elements of China?s irrigation modernization strategy are: [a] total rehabilitation of old, earthen systems into modern, lined canals for high-efficiency irrigation; [b] institutional reform of irrigation management; and [c] total recovery of irrigation fees levied at rates varying from USD 70 to 400/ha. On all these fronts, canal irrigation in India has much ground to cover: the systems are falling apart; the irrigation institutions have declined; and most states fail to recover even token irrigation service fees (ISF). China presents a bold contrast to the Indian scene on irrigation reform.